Specifics of Advertising Communication in the Second Half of 19th Century (by Example of “Nature and Hunting” Magazine) - A. V. Lyapina (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article deals with the genre of advertising on the example of hunting texts extracted from specialized magazines of the second half of the 19th century. Such texts act as a source of interpretation of the hunting subculture in the national picture of the world. The analysis is carried out on the basis of integration of historical-journalistic and linguistic-genre approaches. An attempt is made to trace the evolution of the advertisement genre in the history of the Russian language, as a result of which the advertisement is qualified as a “secondary speech genre.” A communicatively significant characteristic of the genre under consideration is proposed, which contains information about the main genre-forming parameters: intentions, addressee, addresser, structural features. The non-standard and heterogeneity of structural organization of the texts of advertisements about hunting is noted, as part of which the mandatory and variable components of the text structure are distinguished. It is established that one of the optional parameters of the structural organization of the text is an indication of the cost of goods, since advertisements’ authors rely primarily on their quality and prestige, demonstrate the beneficial and strong characteristics of the goods of the hunting sphere. The conclusion is made about the specifics of the language design of advertisements, which is characterized by the use of elements of a specialized terminology system, forms of superlative, means of evaluative vocabulary.